Cost and Cost-Effectiveness of Four Specialized Nutritious Foods for Treatment of Moderate Acute Malnutrition in Sierra Leone (P10-142-19). (13th June 2019) - Shen, Ye; Griswold, Stacy; Langlois, Breanne; Suri, Devika; Vosti, Stephen; Webb, Patrick; Rogers, Beatrice
Abstract: Objectives: To estimate cost-effectiveness of 4 specialized nutritious foods (SNF) for Moderate Acute Malnutrition ( MAM) treatment in children under five in Pujehun District, Sierra Leone Methods: In a cluster randomized trial, a mobile supplementary feeding program was set up at 29 peripheral health units to treat children with MAM (mid-upper arm circumference (MUAC) ≥11.5 cm and <12.5 cm without bipedal edema) with 1 of 4 iso-caloric rations: Corn Soy Blend Plus w/oil (CSB + w/oil, reference), Corn Soy Whey Blend w/oil (CSWB w/oil), Super Cereal Plus w/amylase (SC + A), or Ready to Use Supplementary Food (RUSF). All foods were procured from U.S. except locally produced RUSF. Unlike RUSF and oil provided in commonly programmed specifications, CSB + , CSWB, and SC + A were produced in experimental package size or formulation at small scale. Caregivers picked up rations bi-weekly until children reached an outcome or up to 12 weeks. Collected from accounting records and study instruments using activity-based costing with ingredients, data on 10 components from implementer perspective (start-up, supply chain, and programming) were summarized into cost per enrolled child in 2018 USD for each arm. Other stakeholders' costing perspectives will also be analyzed. To assess cost-effectiveness by arm, cost per recovered child = cost per enrolled child/graduation rate. Predicted means of crude graduation rate (% of children reaching MUAC ≥12.5 cm in 12 weeks) with 95% confidence intervals were estimated from unadjusted mixed-effect model to construct crude cost-effectiveness ranges. Future analyses will be based on adjusted modeling and realistically estimated product costs at scaled production. Results: Children (N = 2681) received similar number of bi-weekly rations by arm. Product and international freight were top drivers of cost differences across arms. Crude graduation rate was not statistically different by arm. Cost per enrolled child ranged from 86 in RUSF to 94 in SC + A. Cost per recovered child was 137 (130 - 145) in RUSF, 142 (134 - 151) in CSB + w/oil, 146 (138 - 155) in SC + A, and 149 (140 - 160) in CSWB w/oil. Conclusions: Crude cost-effectiveness to treat MAM considering only implementer cost was similar across 4 SNFs. Funding Sources: Office of Food for Peace, Bureau for Democracy, Conflict, and Humanitarian Assistance, U.S. Agency for International Development.